Structural crack detection system using internet of things (IoT) for structural health monitoring (SHM): a review - Faisal Nazamuddin; Abdul Hadi Abdul Razak; Nur Shuhada Abdullah; Syed A. M. Al Junid; Abdul K. Halim; Mohd F. M. Idros; Fairul N. Osman (Penerbit Universiti Kebangsaan Malaysia, 2022)
Monitoring the state of civil engineering infrastructure is critical for a country’s economic development since structures with long service life and timely maintenance have lower reconstruction costs. Crack occurrence is the most important element that influences the performance and lifespan of civil infrastructures like bridges and pipelines. As a result, several fracture detection and characterization approaches have been explored and developed in the domains of Structural Health Monitoring (SHM) throughout the last few decades. The major goal of implementing the Internet of Things (IoT) paradigm is to enable the Internet-based connectivity extension of various typical SHM devices. As a result, connected devices can communicate and process data, opening new possibilities in the design of acquisition systems in various disciplines of research and engineering. The researchers have extended the application of the IoT paradigm to the SHM crack detection because of the advances, ensuring that the tests done in this framework can produce good results with promising future improvements. Thus, this paper reviews structural crack detection based IoT for SHM as reported by previous research in the literature. The strengths and limitations of current systems are discussed. This paper is aimed to serve as a reference for crack detection and characterisation researchers as well as others who are interested in SHM in general. In addition, several case studies on real structures, as well as laboratory experiments for monitoring structural crack health of civil engineering structures, are also presented.